Types of Physical Activity and Sports for teens in Maintaining Physical Fitness in Leisure - Desy Tya Maya Ningrum; Herman Chaniago; Ahmad Muchlisin Natas Pasaribu; Yafi Velyan Mahyudi (Universitas PGRI Palembang, 2022)
This study aims to determine the types of physical activities and sports carried out by adolescents in maintaining their physical fitness outside of physical education learning at school. Especially to test the physical activity carried out without using the tool for one month with the number of meetings 10 times. The application of physical activity and exercise is carried out 2 or 3 times per week with a duration of 30 minutes. The research method used is experimental. Participants who took part in this study were 66 students consisting of 45 male students and 16 female students. Physical fitness measurements were carried out using the Yo-Yo Intermittent Endurance Test Level 2. Deeper sports participation, this study divided into outdoor sports and not using tools, both of which were associated with physical activity. The results of this study indicate that the analysis of the mean difference test in the control group obtained t0 of 10.392 and ttable of 2.035 with degrees of freedom (db) 32 and = 0.05. The hypothesis is that there are differences in the average physical fitness of students who are not given physical activity and sports treatment. While the results of statistical analysis of the experimental group obtained t0 of 21.582 and ttable 2.035 with degrees of freedom (db) 32 and = 0.05. The hypothesis is that there are differences in physical fitness in students who are given physical activity and sports treatment. the conclusion is that physical activity and sports support the improvement of physical fitness in adolescent students who are physically active at least once every 2-3 weeks. However, the shortcoming of this study was that it did not see what physical activities and sports the participants did outside of the treatment given.